Impact of Dexamethasone in Improving Outcomes of Laparoscopic Cholecystectomy: A Case- Control Study - Saad Jasim Mohammed; Nashwan Mohammed Rajab; Wissam Jassim Naif (Zien Journals, 2023)
Postoperative nausea and vomiting (PONV) remains a matter of concern for surgeons as they induce dehydration, metabolic abnormalities, delayed recovery, and other problems. It has been shown that dexamethasone can contribute to the reduction of postoperative symptoms. Therefore, this study aimed to evaluate the protective role of dexamethasone in reducing postoperative nausea and vomiting in patients who underwent laparoscopic cholecystectomy (LC) through comparison with antiemetic metoclopramide
Keywords: Cholecystectomy; dexamethasone; nausea; vomiting